PENGARUH PEMBERIAN KURMA TERHADAP PENINGKATAN KADAR HAEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA - Ginting, Wira Maria (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Giving dates is an action to increase hemoglobin levels in pregnant women who are experiencing iron anemia. The type of date given is in the form of ajwa dates or what is usually known as the Prophet's date, which is a type of date that grows in Saudi Arabia and is well-known. The purpose of this study was to determine the effect of giving dates on the increase in hemoglobin levels in pregnant women with anemia at the Batang Beruh Public Health Center, Sidikalang District in 2020. The research method used a quantitative research design with a quasi experimental type. With one group test in which the respondents studied were only 1 group where the group had their Hb measured before they were given dates and their Hb was measured again after being given dates. The results of the study were obtained based on the analysis of the Paired T-test, it was obtained p-value = 0.000 <a = 0.05, so the research hypothesis was accepted, so it could be concluded that there was an effect of giving dates on an increase in hemoglobin levels in pregnant women with anemia at the health center Beruh Sidikalang district, Dairi district in 2020. Conclusion: pregnant women before being given a low hemoglobin level were 44 people (100%), and pregnant women after being given dates had high hemoglobin levels as many as 44 people (100%). Suggestion: for future researchers It is hoped that this research can add input for further researchers to add research variables.